BACTERIAL EXOPOLYSACCHARIDE-MEDIATED GREEN SYNTHESIS OF IRON OXIDE NANOPARTICLE AND ITS EFFECT ON BACTERIAL BIOFILM (Applied Biological Research, 2025)
Biofilm acts as a protective shield for planktonic bacteria, enabling them to develop tolerance against antibacterial drugs. Escherichia coli and Bacillus subtilis are among the primary biofilm-forming bacteria, producing an exopolysaccharide (EPS) matrix in which planktonic cells become embedded to form structured biofilms. In the present study, iron oxide nanoparticles (NPs) were synthesized using bacterial EPS and their antibiofilm activities against E. coli and B. subtilis were evaluated. Two types of nanoparticles, GFNB (synthesized using B. subtilis EPS) and GFNE (synthesized using E. coli EPS), were developed via an EPS-mediated hydrothermal method. The nanoparticles were characterized using UV-Vis spectroscopy, FTIR, XRD, and TEM. TEM analysis revealed that the crystalline iron oxide NPs had sizes of less than 5 nm (GFNB) and less than 2 nm (GFNE). The NPs inhibited planktonic bacterial growth at concentrations of 1.3 µg/mL and 3.2 µg/mL (GFNB and GFNE, respectively) against E. coli, and at 3.2 µg/mL and 4.2 µg/mL (GFNB and GFNE, respectively) against B. subtilis. Moreover, the NPs demonstrated significant inhibition of biofilm formation and facilitated the dispersion of sessile cells even at sub-inhibitory concentrations. This study highlights a green synthesis approach to producing iron oxide nanoparticles using bacterial EPS, offering an effective strategy for antibiofilm applications.
Keywords: Biofilm; dispersion; characterisation; iron oxide nanoparticle; TEM